Cytokine profiling in plasma distinguishes the histological inflammatory subtype of head and neck squamous cell carcinoma and a novel regulatory role of osteopontin - Ghita, Ioana; Piperi, Evangelia; Atamas, Sergei P.; Bentzen, Soren M.; Ord, Robert A.; Dyalram, Donita; Lubek, Joshua E.; Younis, Rania H. (Frontiers in Oral Health, 2022)
Head and neck squamous cell carcinoma (HNSCC) can be classified according to the histological inflammatory subtype (HIS) into inflamed (HIS-INF) or immune excluded (HIS-IE). HIS-IE was previously associated with higher levels of soluble Semaphorin 4D (HsS4D) in plasma, and higher transcriptional levels of osteopontin (OPN) in the tumor tissue, compared to HIS-INF. The goal of the current study is to investigate whether the HIS inflammatory subtype can be distinguished by a differential cytokine panel in peripheral blood. Retrospectively collected five HIS-INF and five HIS-IE tumor tissue with paired plasma were included in the study. Five healthy donors (HD) and five autoimmune/chronic inflammatory conditions (AI/CI) were controls. The ELISA-Luminex™ system was used to detect 40 traditional cytokines in plasma. Human cytokine array (104 cytokines) was used for the conditioned medium (CM) of the HNSCC HN6 cell line. Semaphorin 4D (Sema4D) siRNA and recombinant human osteopontin (rh-OPN) were used to investigate the effect of OPN on Sema4D expression. The HIS-IE cytokine profile was higher than HIS-INF but comparable to AI/CI. HIS-INF had the lowest cytokine levels. HIS-IE was differentially higher in IP-10 and IL8 compared to HD, while HIS-INF was higher in IL-10. Sema4D inhibition in HN6 resulted in a decrease of OPN in the CM of HN6, and treatment with rh-OPN rescued Sema4D in HN6 cell lysate and associated CM. In conclusion, the current work demonstrates a novel association between the HIS subtypes and a differential pattern of cytokine expression in plasma. These findings can open new avenues for HNSCC patient stratification and hence provide better personalized treatment.